Hydration and Hardening Properties of High Fly-Ash Content Gel Material for Cemented Paste Backfill Utilization - Bolin Xiao; Jiandong Wang; Aixiang Wu; Ruiming Guo (Gels)
As more and more mines utilize the cemented paste backfill (CPB) mining method, the demand for reducing backfill cost and carbon footprint is increasing and becoming more critical. In this work, a new backfill gel binder made with 40 wt.% of low-quality Class F fly ash (FCM) is proposed to replace ordinary Portland cement (OPC). The binder hydration and gel hardening properties were experimentally investigated through X-ray diffraction, Mercury intrusion porosimetry, uniaxial compression, and thermogravimetric analysis. Three different mine tailings were used to verify the FCM’s applicability. Results show that the strength performance of FCM-CPB is 72% of that of OPC-CPB, while FCM production cost is almost less than half of OPC. The hydration process of the FCM-CPB can be divided into five stages, and the main hydration products are ettringite and gel-like hydrates. The 31.2% porosity of FCM-CPB at 28-day curing is higher than that of 7-day curing, while the average pore size is lower, and the structure is denser. The FCM can meet the strength requirement of three different mine tailings regarding different subsequent filling and cut-and-fill mining methods. The proposed FCM provides a feasible alternative with economic and environmental benefits.